Assessment of Doppler waveform patterns and flow velocities of hepatic veins in children with acute viral hepatitis - Murat, Ayşe; Akarsu, Saadet; Cihangiro?lu, Mutlu; Yildirim, Hanefi; Serhatlio?lu, Selami; Kalender, Ömer (My University, 2006)
Purpose: To evaluate hepatic vein flow patterns and velocities in children with acute viral hepatitis and to compare the findings to a group of healthy children, with duplex sonography. Materials and methods: Forty children with acute viral hepatitis were enrolled in group 1 and forty healthy children were enrolled in group 2 (control group). Both groups underwent gray scale and duplex sonography. Hepatic venous Doppler flow patterns were categorized as triphasic, biphasic, or monophasic. Peak systolic velocities of hepatic veins were recorded. Results: In group 1, hepatic venous flow was triphasic in 61. 6%, monophasic in 26.6%, and biphasic in 11.6% of the patients. These figures were 88.3%, 8.3%, and 3.3%, respectively, for the controls in group 2. Group 1 had fewer patients with only a triphasic flow pattern, but had a higher percentage of monophasic and biphasic flow patterns. There was a triphasic flow pattern in all three hepatic veins in 50% of group 1 and in 80% of group 2. Differences in flow patterns of hepatic veins between the groups were found to be significant according to the student t-test (p<0.01), and this was independent of age, gender, feeding status, and activity. Conclusion: Similar to reports of chronic liver disease or diffuse liver disease, significant differences in the flow patterns of hepatic veins were found in children with acute viral hepatitis. Hepatic vein flow patterns were frequently monophasic or biphasic in group 1, especially when accompanied by change in hepatic echogenicity. There was no significant difference in the flow velocities of the hepatic veins between group 1 and group 2. © Turkish Society of Radiology 2006.
Keywords: Acute viral hepatitis; Children; Duplex sonography